A Comparative Review of Climate Mobilization Plans - Korhonen Janne M.; Karvinen Juho (Germany, 2022)
Continuing failure of climate mitigation efforts to produce results has directed scholarly and public interest towards those episodes in human history where governments have enacted emergency measures for the common good. In particular, the experience of the industrial mobilization to the Second World War has been cited increasingly often as a possible model for emergency climate efforts. In this paper, we review the most notable “climate mobilization” proposals from the first explicit war mobilization parallel in 2001 to recent booklength treatments. We outline the common themes and suggest further research to the topic is warranted.
Proceedings of the Conference on Technology Ethics Turku, Finland, October, 20-22, 2021